Characterization of the cystic fibrosis transmembrane conductance regulator in a colonocyte cell line. - Cohn, J A (1992)
An anti-peptide antibody raised to the C-terminal sequence of the cystic fibrosis transmembrane conductance regulator (CFTR) was used to examine CFTR immunoreactivity in the T84 colonocyte cell line. Immunoblots of T84 cell lysates detected CFTR as a 170-kDa protein that appeared as a broad band or doublet in SDS/PAGE. This protein comigrated with the predominant immunoblot signal detected in human pancreas and colon. An equivalent protein was detected as a prominent substrate for protein kinase A and for protein kinase C in T84 cell immunoprecipitates with this antibody. The immunoprecipitated protein resembled the protein detected by immunoblot in that both proteins showed the same change in electrophoretic mobility after digestion by N-Glycanase. The precipitated protein was indentified as CFTR by two criteria. First, the same protein was immunoprecipitated with an antibody to a different CFTR peptide, [Lys102]CFTR-(102-116). Second, two-dimensional phosphopeptide mapping was used to compare the immunoprecipitated protein with a bacterially expressed protein known to contain most of the predicted protein kinase A phosphorylation sites in CFTR. Because the six most prominent peptides in each map were equivalent, these maps confirm that the precipitated protein is CFTR. By using these antibodies for immunofluorescence and immunoperoxidase staining, CFTR was localized to the apical region of T84 cells grown in tumors and in monolayers. Thus, T84 cells express CFTR at sufficient levels to permit identification and immunochemical studies of this protein in its endogenously occurring form.